Diseño de un mercado agrícola - artesanal para el cantón bolívar, situado en la parroquia urbana de calceta - Calderón Cedeño, Jorge Luis (2024)
The Bolívar canton, located in the province of Manabí, stands out for the fertility of its soils, especially in its three parishes. Calceta stands out with 15.58% in the crop, followed by Membrillo with 13.02% and Quiroga with 6.01%. This characteristic makes the region a favorable area for agriculture. Although less known, manufacturing is a topic of great relevance. The progressive loss of agricultural and artisanal labor is evident due to the lack of adequate space for its promotion and sale at the local, national and international level. In the urban parish of Calceta, various difficulties are faced in the commercial field\; both formal and informal merchants from various urban and rural areas, including Quiroga, Membrillo and Calceta, lack a formal center for the commercialization of their products. This situation contributes to deculturalization and disorganization on the main roads of the city. Therefore, it is imperative to carry out immediate intervention to boost the commercial sector and revitalize manufacturing, which is an integral part of the local culture. This project would not only benefit merchants, but would also become a tourist attraction for both residents and foreign visitors. Faced with these fundamental elements, the creation of a Collection Center and an Agricultural-Artisan Shopping Plaza based on bioconstruction and passive design is proposed in the urban parish of Calceta, in the Bolívar canton of the Province of Manabí. This project seeks to integrate local culture in an architectural and urban space appropriate for this type of activities.